(untitled) (LACCEI, 2024)
This paper deals with the design, tests, and results obtained by implementing a D-STATCOM prototype. The process is detailed from the point of view of the design, going to the operation of the D-STATCOM and ending with the design of the prototype. Finally, an analysis of the tests and results obtained is carried out to validate the design and the developed prototype.